Housing the co-op a micro-political manifesto - Delz, Sascha 1979-; Hehl, Rainer; Ventura, Patricia (Ruby Press, 2020)
Since 2008, there has been a renewed search for alternative forms of housing production that can move beyond speculative interests and are based instead on models of co-ownership, co-production, and co-management. Hence the concept of the cooperative has experienced a true renaissance in recent years. This book explores how cooperative housing construction and forms of self-determined building production might offer effective solutions to the global housing crisis, moving us closer to a more equitable and sustainable future through systematic change. With case studies from Germany, Switzerland, Brazil, Uruguay, Ethiopia, and China, as well as a glossary of important terms
Keywords: Wohnungsbaupolitik; Kollektive Wohnform; Wohnungsbaugenossenschaft; Baugemeinschaft; Internationaler Vergleich